1993
DOI: 10.15173/esr.v5i2.302
|View full text |Cite
|
Sign up to set email alerts
|

Is the World Oil Market "One Great Pool"? A Test

Abstract: In a recent paper Professor Robert

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Adelman observed that the world's oil market was highly globalised and integrated, a claim that Rodriguez and Williams verified [5]. Nevertheless, there is still controversy surrounding the convergence and divergence of the international oil market.…”
Section: Introductionmentioning
confidence: 99%
“…Adelman observed that the world's oil market was highly globalised and integrated, a claim that Rodriguez and Williams verified [5]. Nevertheless, there is still controversy surrounding the convergence and divergence of the international oil market.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the previous studies that found the price of ANS was cointegrated with the price of WTI. Gülen (1997) and Rodriguez and Williams (1993). Table 2 presents parameter estimates using IV and OLS estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Formally, two nonstationary stochastic processes various other crude oils traded on the world market. Gülen (1997) and Rodriguez and Williams (1993) both found that ANS is cointegrated with other crude prices.…”
Section: [Figure 4 About Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in my original paper , questions of market definition have received inadequate attention in the energy area, and more contributions are most welcome, as is debate over empirical methodology and interpretation of results. Unfortunately, the paper by Rodriguez and Williams (1993) in the preceding issue of Energt) Studies Re-view contains serious flaws, rendering its conclusions of doubtful use for addressing energy policy questions. This brief reply explains why…”
Section: Introductionmentioning
confidence: 99%